MEWARNAI GAMBAR HEWAN DAN BERMAIN PERAN BERSAMA ANAK PAUD TUNAS HARAPAN, DESA NAPAN - Simarmata, Yohanes Timbun Raja Mangihut Ronael; Ngadha L., Maria Emerentiana; Kale, Maria Laurenci Fanny Permata; Tangkonda, Elisabet (Jurnal Media Tropika, 2025)
Animal coloring and role-playing activities carried out at PAUD Tunas Harapan, Napan Village, aim to stimulate the cognitive, social emotional, and motor development of early childhood. Through this activity, children are invited to get to know various types of animals, develop their imagination, and train their motor skills. The results of implementing the activity show that it can improve children's ability to recognize colors, shapes, and the names of animals. In addition, children become more active and creative. Thus, it can be concluded that coloring and role-playing activities are effective learning methods for developing various aspects of early childhood development.